Representation of Teachers in Turkish Cinema Between 1940 and 1980 - Murat Cem Acaralp; Fevzi Kasap; Mustafa Ufuk Çelik (CINEJ Cinema Journal, 2023)
The film of the destruction of the Russian monument in 1914 is not only the history of Turkish cinema, but also of a country. The aim of this study is to reveal the representation of teachers in Turkish cinema, which is one of the professions that shape a nation, in films that reflect the effects of the periods spent in all its positive and negative aspects. The reflections of the political and social changes experienced in the historical process on the cinema, the emphasis in the representation of the teacher and the quality of the added value created in the society were analyzed in comparison with the periodical conjuncture. With the purposeful sampling management, the films in which the teacher was represented from 1940 to 1980 were compared with the conditions of the period in which they were shot, and their reflections on the society and the teacher were examined.